Ambedkar’s Views on Social Justice - Dr. Vinod Kumar (Studies in Law and Justice, 2024)
Social justice is an application of distributive justice to wealth, assets, privileges and advantages within a society or a state. The essence of justice is the attainment of common good for all. Social justice involves the creation of a just and fair social order and provides justice for every member of the community. Social justice in India is the product of social injustice of the caste system. Such social inequalities pose a serious threat not only to society but also to Indian democracy. Under the traditional Hindu caste hierarchy, backward communities and women have suffered for centuries because they were denied equality, education and other opportunities for advancement. For B. R. Ambedkar, the concept of social justice stood for liberty, equality and fraternity for all human beings. He advocated a social system based on equalization in society among individuals in all spheres of life. Being trained as a social scientist, he acquired deep knowledge in every field of human activity to become a founder of his own independent ideology. He understood social, political, religious and economic problems as associated with caste and the position of women in Indian society. His ideology and beliefs are important for social progress and stability of the Indian society. In this research paper have discuss Ambedkar’s views on social justice.